2009
DOI: 10.1097/fjc.0b013e3181c5e7fd
|View full text |Cite
|
Sign up to set email alerts
|

Olive Oil and Cardiovascular Health

Abstract: The Mediterranean diet, in which olive oil is the primary source of fat, is associated with a low mortality for cardiovascular disease. Data concerning olive oil consumption and primary end points for cardiovascular disease are scarce. However, a large body of knowledge exists providing evidence of the benefits of olive oil consumption on secondary end points for the disease. Besides the classical benefits on the lipid profile provided by olive oil consumption compared with that of saturated fat, a broad spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
93
1
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(98 citation statements)
references
References 74 publications
1
93
1
3
Order By: Relevance
“…[4][5][6][7] Olive oil is a rich source of oleic acid. 8 However, it has been suggested that the beneficial effects of its consumption in the prevention of chronic diseases may not only be attributed to its fatty acid composition but also to its high content of phenolics. [9][10][11] Studies in cultured cells [12][13][14][15][16][17][18][19] and laboratory animals [20][21][22][23] have demonstrated that the olive oil phenolics tyrosol, hydroxytyrosol, and oleuropein exert antioxidant, antiinflammatory and gene regulatory activities.…”
mentioning
confidence: 99%
“…[4][5][6][7] Olive oil is a rich source of oleic acid. 8 However, it has been suggested that the beneficial effects of its consumption in the prevention of chronic diseases may not only be attributed to its fatty acid composition but also to its high content of phenolics. [9][10][11] Studies in cultured cells [12][13][14][15][16][17][18][19] and laboratory animals [20][21][22][23] have demonstrated that the olive oil phenolics tyrosol, hydroxytyrosol, and oleuropein exert antioxidant, antiinflammatory and gene regulatory activities.…”
mentioning
confidence: 99%
“…Ample evidence in literature indicates that olive oil can be recommended to hypertensive patients because it is rich in heart-healthy monounsaturated fats and phenolic antioxidants [44,45]. For palm oil, past studies that were conducted to assess its effect on blood pressure levels were mainly carried out on rats [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…O efeito adverso ocasionado pela elevada ingestão de AGPI também pode ser um aumento de produtos intermediários, como peróxidos e aldeídos, o que pode acarretar danos localizados nas membranas celulares, formação de Espécies Reativas de Oxigênio (ERO), oxidação de lipídeos de membrana, proteínas, enzimas, carboidratos e Deoxyribonucleic Acid (DNA), prejudicando o equilíbrio e gerando o estresse oxidativo ou danos oxidativos 4 , e consequentemente, um quadro inflamatório no organismo humano e animal 5 .…”
Section: N T R O D U ç ã Ounclassified